The Neolithic in transition — how to complete a paradigm shift. (November 2013) - Watkins, Trevor
Abstract : As archaeologists, we are accustomed to the appearance of lots of new information that constantly requires us to adjust, or change, our understanding of the period, region or subject in which we are interested. But we are much less competent in upgrading or revising the frameworks within which we form those understandings. Here, I take terms like Neolithic, Pre-Pottery Neolithic A (PPNA) and Pre-Pottery Neolithic B (PPNB), that were formed as extensions into the southern Levant of Gordon Childe's mid-20th-century culture-history methodology, and show that they are now outdated and unhelpful; indeed, I argue that they are obstacles to the formation of a general understanding of the complex processes in which we are interested. The culture-history framework was spatial as well as chronological; and too much of the discussion with which our learned journals are clogged derives from the pointless quest to continue the tradition of the spatial mapping of cultures. Here, I argue that we need (a) a simple, continuous chronological sequence whose blocks of time are numbered back from the late 4th millennium BC to at least the Upper Palaeolithic-Epipalaeolithic boundary around 23, 000 years ago; and (b) a bottom-up, social network-based mode of investigating and discussing the different levels of socio-cultural networking in which people were engaged, the highest level of which was what we have mistakenly called the archaeological culture.